Petrogenetic study of glaucophane schists and associated rocks from the Ile de Groix, Brittany, France - Carpenter, M (1976)
The metamorphic rocks of the He de Groix are classified into four groups: Aluminous schists Banded epidote schists Magnesian schists Massive metabasic schists which are then subdivided on the basis of observed mineral paragenesis. Rocks of presumed igneous parentage (including the banded epidote schists, massive metabasic schists and some albitic aluminous schists) were selected for detailed chemical and mineralogical investigation, and twenty new whole rock analyses (major and trace elements) are given. Of the twenty analysed rocks, eight provided material for original microprobe analyses of the constituent minerals and sixteen were analysed for their Sr isotopic composition. Co-existing phengite, glaucophane, epidote and impure barroisite were separated from one of the analysed rocks (a glaucophanic eclogite) and used to obtain K-Ar and Rb-Sr (mineral isochron) radiometric ages. This dating work was supplemented by the inclusion of original K-Ar analyses on phengites and glaucophanes from aluminous and epidote banded schists, separated and provided by previous workers. The phengite separates, for which published analyses are available, were also used to yield Rb-Sr model ages. On the basis of mineral parageneses observed in metabasic schists, the lie de Groix is divided into two metamorphic zones, I and II, separated by a 'garnet-in-metabasics' isograd. In zone I are confined the phyllitic chloritoid schists and glaucophane bearing metabasic schists without garnet. Zone II contains garnet bearing porphyroblastic chloritoid schists and boudins of glaucophamic eclogite. Within the two metamorphic zones so defined, the sequence of mineral growth in contrasting lithologies is inferred from thin section textural studies. This sequence of mineral growth is then related to the development of fabric elements within the rock, as deduced from outcrop scale observations of fold style and schistosity. Four phases of, deformation are defined, using the criteria of re-folded folds and schistosities, and these are used as a relative time framework against which mineral growth episodes are compared. F1 deformation, characterised by flat lying, highly flattened isoclines and boudins, is dominant in the higher grade zone II, and F2 characterised by open, upright folding, is dominant in zone I. In the boundary zone between the two zones, fold interference is very common. Glaucophane growth in the metabasic schists is inferred to be mostly syn Fsub>1 deformation, though the lack of straining suggests mimetic crystallization. The possibility of a glaucophane + lawsonite paragenesis during early syn- deformational phase of metamorphism in zone II is strongly supported by the occurrence of pseudomorphs after lawsonite which contain euhedral, post- tectonic garnets. Omphacite is thought to have crystallized in water- deficient assemblages after the breakdown of lawsonite and the beginning of garnet growth. Thus, the garnet + omphacite equilibrium assemblages are not relict from a pre-glaucophane schist metamorphism, but represent the peak of dry, prograde metamorphism in the metabasic rocks of Groix. The conditions of metamorphism for the Groix blueschists are inferred from the comparison of natural, microprobed parageneses with published experimental mineral stability and element partitioning data. Pressure/ temperature estimates for the metamorphism of the glaucophanic eclogites are derived from the Fe/Mg partitioning between adjacent garnet and clinopyroxene rims and from the jadeite content of omphacite in equilibrium with quartz and albite. This method gives an intersection of equilibria at 400 ± 50°C and 8 ± 1.5 kb pressure, which is consistent with blueschist facies rocks from New Caledonia and Japan, and suggests that metamorphism took place in a region of low geothermal gradient (ca. 15°C/km if density = 2.9 g.cm<sup-3< sup=""> ) - possibly in a subduction zone.</sup-3<> Ferroglaucophane is commonly observed in the metabasic schists of zone I, and sometimes as inclusions in zone II garnets. From the rather restricted known temperature/fO2 stability of ferroglaucophane, it is possible to say that during metamorphism of the zone I metabasics, temperatures never rose more than about 390 ± 10°C at oxygen fugacities on the QFM buffer near 10-30 bars. The T-XC02 stabilities of lawsonite and rutile/sphene place a constraint of XCO2 < 0.03 during -prograde metamorphism of the basic rocks. A 'retrogressive' phase of metamorphism is proposed, associated with the deformation phases F3 and F4, and is characterised by increased fO2 (10-20 bars) decreased load pressure, and possibly higher temperatures (450 - 500 °C). These conditions are derived from the alteration of ferroglaucophane to magnetite, albite and quartz and the lack of kyanite development in aluminous rocks. Other effects of the 'retrogression' are the replacement of garnet, omphacite and glaucophane by barroisite, the alteration of garnets to chlorite and the infilling of cavities and veins with pegmatitic chlorite, albite and quartz. By extension, the massive chlorite + albite greenstones are thought to have developed during the 'retrogression' whenever water was available in sufficient quantities to allow recrystallization of the whole rock mass. The Sr isotope compositions and present day Rb/Sr values of sixteen analysed rocks were used to place constraints on the original age of eruption of the Groix volcanics, which is thought to lie between 400 and 500 Myr ago. Fourteen of the rocks so used are metabasic, and three original magma type groups are recognised on the basis of trace element contents and discriminant analysis. One magma-type is common amongst the metabasics of zone II, and is characterised by Mid-Ocean ridge type chemistry and bimodal Ti02 contents. Other magma types have more alkaline affinities, and a large range in 87Sr/85Sr initial ratio 400 Myr ago is postulated (0.704 - 0.711). The concordance of K-Ar dates for two olaucophane-phergite pairs from widely separated aluminous and basic schist outcrops with the Rb-Sr mineral isochron (Epidote-whole rock-phengite) for a glaucophanic eclogite is interpreted as resulting from short-lived prograde mineral growth 340 ± 10 Myr ago throughout Groix. Barroisite overgrowths on glaucophane are found to be significantly younger by about 40 Myr than the prograde metamorphic assemblage. The age of this late 'retrogression' (295 ±: 8 Myr) corresponds with uplift and cooling ages throughout the Hercynides, and was probably brought about by thermal relaxation to a more normal geothermal gradient (i.e. 30°C/km), during rapid uplift, after subduction ceased.